Quadratic stochastic operators on segment [0,1] and their limit behavior - Ganikhodjaev, Nasir; Hamzah, Nur Zatul Akmar (Indian Society for Education and Environment & Informatics Publishing Limited, 2015)
In this paper, we construct some class of quadratic stochastic operator defined on continual state space [0, 1], and show that such operators are regular transformation.